Dostop do elektronskih virov - Pokorn, Daša (Organizacija znanja, 2009)
The Digital Library of Slovenia operates within the framework of the National and University Library. www.dlib.si is a portal for knowledge management, and it is constantly being developed and improved according to users' needs and current standards. The Digital Library of Slovenia fulfils its basic mission, which is the same as any library's, to which achievements of the past years are the prof. It is connected with similar projects in Europe and contributes significantly to the recognition of the Slovenian cultural heritage. It cooperates with home establishments, educational institutions and other important partners. As a provider of the broadest coverage of and open access to digital cultural and scientific digital content, the Digital Library of Slovenia remains, and more and more it also becomes, a key factor in the democratization of the society and the basis of its progress.
Keywords: culture; Digital Library of Slovenia; digitalizacija; Digitalna knjižnica Slovenije; digitalne knjižnice; digitalni arhivi; digitization; e-vsebine; informacijski portali; kultura; Narodna in univerzitetna knjižnica; National and University Library of Slovenia; portal dLib.si